2021
DOI: 10.21873/invivo.12446
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Blood Plasma Free-amino Acid Levels in Infertile Men

Abstract: Japan) (17), and a p-value <0.05 was considered statistically significant. Differences between groups were compared using the Mann-Whitney U-test and Kruskal-Wallis test. *Values are presented as median (range).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Zhao et al found reduced levels of several amino acids, such as leucine (Leu), glutamic acid (Glu), and Trp, in patients with weak spermatozoa [ 58 ]. Another study found lower levels of tryptophan and glutamate in men with lower sperm motility and higher rates of morphological abnormalities [ 59 ]. In the present study, the levels of Trp (FC = 2.29, p < 0.001), Glu (FC = 2.88, p < 0.001), and Leu (FC = 2.95, p < 0.001) in the seminal plasma were also significantly lower in the LM group than in the HM group.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al found reduced levels of several amino acids, such as leucine (Leu), glutamic acid (Glu), and Trp, in patients with weak spermatozoa [ 58 ]. Another study found lower levels of tryptophan and glutamate in men with lower sperm motility and higher rates of morphological abnormalities [ 59 ]. In the present study, the levels of Trp (FC = 2.29, p < 0.001), Glu (FC = 2.88, p < 0.001), and Leu (FC = 2.95, p < 0.001) in the seminal plasma were also significantly lower in the LM group than in the HM group.…”
Section: Discussionmentioning
confidence: 99%